KEPARAHAN PENYAKIT BUSUK BUAH KAKAO (Phytophthora palmivora Butl.) PADA BEBERAPA PERKEBUNAN KAKAO RAKYAT YANG BERBEDA NAUNGAN DI KABUPATEN LANGKAT - Akhmad Fauzan; Lahmuddin Lubis2 Lahmuddin Lubis2; Mukhtar Iskandar Pinem (Universitas Sumatera Utara, 2013)
Disease severity of cocoa black pod (Phytophthora palmivora Butl.) at several smallholder’s cocoa plantations with different shade in Langkat district. The study aims to calculate the disease severity of cocoa black pod (P. palmivora) at several smallholder’s cocoa plantations with different shade in Langkat district. The study was conducted in five smallholder’s cocoa plantations that have different shade in Langkat, which is unshaded cocoa plantation at Karang Anyar village, Secanggang sub-district, suren shaded cocoa plantation at Karang Anyar village, Secanggang sub-district, banana shaded cocoa plantation at Sambirejo village, Binjai sub-district, palm oil shaded cocoa plantation at Sambirejo village, Binjai sub-district, mixed shaded cocoa plantation at Tanah Seribu village, Sei Bingai sub-district with altitude ± 28 m asl and at the Laboratory of Plant Disease Faculty of Agriculture, University of North Sumatera with altitude ± 25 m asl. The method of research is survey. Results showed that highest disease severity of black pod rot found at cocoa that shaded by bananas located in Sambirejo village, Binjai sub-district which reach 73.40 %, and the lowest was founded at cocoa plantation that shaded by suren located in Karang Anyar village, Secanggang sub-district which reach 12.80 %. Keywords : severity, Phytophthora, cocoa, shade.